605. Loneliness Among Older Adults Living with HIV: A Study and Online Community. (26th November 2018) - Kane, Mark; Mazonson, Peter; Zolopa, Andrew; Spinelli, Frank; Ferrer, Pedro Eitz; Shalit, Peter
Abstract: Background: The population of people living with HIV (PLHIV) is aging. A new registry and online community, called Aging with Dignity, Health, Optimism and Community (ADHOC), has been launched to investigate how HIV impacts the lives of older PLHIV. Methods: A cross-sectional analysis of ADHOC was performed on 208 PLHIV 50+ years of age. One hypothesis was that increasing age would be associated with greater loneliness. Loneliness was assessed using the UCLA Loneliness Scale (ULS-3). A score ≥6 was classified as lonely. The impact of aging on loneliness was analyzed by ANOVA and multiple linear regression. Results: ULS-3 scores ranged from 3 to 9 and 48.6% of subjects were classified as lonely. Significant differences were found between the 50–59, 60–65 and 65+ age groups, with older age associated with decreased loneliness ( P = 0.018) (Table 1). In the multiple linear regression model, these observations persisted even after controlling for gender, sexual orientation, race/ethnicity, relationship status, education, income, and number of comorbidities (Table 2). Decreases in loneliness were associated with female gender, being in a relationship, higher income, and fewer comorbidities ( P < 0.05). Conclusion: Among PLHIV over 50, loneliness is less severe in older age groups. Additional investigation is needed to better understand potential causes and to find ways to remediate loneliness among older PLHIV. Disclosures: M. Kane, ViiV Healthcare: Research Contractor, Research grant and Research support. Mazonson & Santas, Inc.: Employee, Salary. P. Mazonson, Mazonson & Santas, Inc.: Co-Founder and Shareholder, Salary. ViiV Healthcare: Investigator and Research Contractor, Research grant and Research support. A. Zolopa, ViiV Healthcare: Employee, Salary. F. Spinelli, ViiV Healthcare: Employee, Salary. P. Eitz Ferrer, ViiV Healthcare: Employee, Salary. P. Shalit, Gilead: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium. Viiv: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. Janssen: Consultant, Investigator and Speaker's Bureau, Research support and Speaker honorarium. Merck: Speaker's Bureau, Speaker honorarium.